1984
DOI: 10.1128/mcb.4.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone increases the number of RNA polymerase II molecules transcribing integrated mouse mammary tumor virus DNA and flanking mouse sequences.

Abstract: In mouse Ltk-cells that were transfected with recombinant bacteriophage DNA containing a complete proviral copy of an integrated endogenous mouse mammary tumor virus (MMTV) with its flanking cellular sequences, the newly acquired MMTV proviruses were transcribed in a glucocorticoid-responsive fashion. After hormone treatment of selected cell clones in culture we isolated the nuclei, elongated the nascent RNA chains in vitro, and determined the number of RNA polymerase II molecules on the transcribed MMTV DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Although the phenomenon that steroid hormones induce gene expression levels in a dose dependent manner is well known (Ringold et al, 1977;Young et al, 1977;Ucker et al, 1981Ucker et al, , 1983Groner et al, 1983;Firzlaff and Diggelmann, 1984), there have been no published reports that distinguish whether this dose dependence is a response of individual templates or of the mass of the templates. Since typical eukaryotic cells have just two templates in a single cell and the phenotypes of the cells are determined at a single cell level, a differentiation between these two possibilities seems to be fundamentally important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the phenomenon that steroid hormones induce gene expression levels in a dose dependent manner is well known (Ringold et al, 1977;Young et al, 1977;Ucker et al, 1981Ucker et al, , 1983Groner et al, 1983;Firzlaff and Diggelmann, 1984), there have been no published reports that distinguish whether this dose dependence is a response of individual templates or of the mass of the templates. Since typical eukaryotic cells have just two templates in a single cell and the phenotypes of the cells are determined at a single cell level, a differentiation between these two possibilities seems to be fundamentally important.…”
Section: Discussionmentioning
confidence: 99%
“…Possible regulatory steps directly related to heterogeneous gene induction It is well established that the dose dependent increase of the gene expression level by the MTV enhancer/promoter occurs at the transcription level (Ringold et al, 1977;Young et al, 1977;Ucker et al, 1981Ucker et al, , 1983Groner et al, 1983). More directly, Firzlaff and Diggelmann (1984) showed that this is caused by a specific dose dependent increase in the RNA polymerase II loading after hormone treatment. Thus, it is reasonable to infer that the current phenomenon, a dose dependent increase in responding cells, occurs at the transcription level.…”
Section: Heterogeneous and Dose Independent Glucocorticoid Induction mentioning
confidence: 99%
“…Transcription from the proviral DNA of mouse mammary tumor virus (MMTV) is controlled by steroid hormones (1,2) through their binding to receptor proteins and the interaction of hormone-receptor complexes with regulatory DNA sequences, thereby causing an increase of the number of active RNA polymerase II molecules on the MMTV promoter (3). The hormone-responsive sequences are located in the long terminal repeat (LTR) of the provirus (4,5,6,7), in a region of approximately 200 bp upstream of the transcription start site (8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…transfected cells leads to an increase in the level of RNA polymerase II molecules, initiating transcription at the MMTV LTR promoter (16), and to an approximately 100-fold accumulation of the corresponding specific mRNA (6).…”
mentioning
confidence: 99%